A facility solution required to incorporate cold sterilisation in the supply chain of citrus exported to Europe - Le Roux, Hester (University of Pretoria. Faculty of Engineering, Built Environment and Information Technology. Dept. of Industrial and Systems Engineering, 2019)
Mini Dissertation (B Eng. (Industrial and Systems Engineering))--University of Pretoria, 2017.